Informing healthcare operations with integrated pathology, clinical, and epidemiology data: Lessons from a single institution in Kenya during COVID-19 waves - Njau, Allan; Kimeu, Jemimah; Gohil, Jaimini; Nganga, David (Frontiers in Medicine, 2022)
Pathology, clinical care teams and public health experts often operate in silos. We hypothesized that large data sets from laboratories when integrated to other healthcare data can provide evidence that can be used to optimize planning for healthcare needs, often driven by health seeking or delivery behavior. From the hospital information system, we extracted raw data of tests performed from 2019 to 2021, prescription drug usage and admission patterns from pharmacy and nursing departments during the Covid-19 pandemic in Kenya (March 2020 to December 2021). Proportions and rates were calculated. Regression models were created and T-test for differences between means were applied for monthly or yearly clustered data compared to pre-Covid-19 data. Tests for malaria parasite, Mycobacterium tuberculosis, rifampicin resistance, blood group, blood count and histology showed statistically significant decrease in 2020, followed by partial recovery in 2021. This pattern was attributed to restrictions implemented to control the spread of Covid-19. On the other hand, D-dimer, fibrinogen, CRP, and HbA1c, showed statistically significant increase (p-value <.001). This pattern was attributed to increased utilization related to the clinical management of Covid-19. Prescription drug utilization revealed a non-linear relationship to Covid-19 positivity rate. Results from this study reveal the expected scenario in the event of similar outbreaks. They also reveal the need for increased efforts at diabetes and cancer screening, follow-up of HIV and tuberculosis patients. In order to realize a broader healthcare impact, pathology departments in Africa should invest in integrated data analytics, for non-communicable diseases as well.